A produção de biocombustíveis: uma análise econométrica dos efeitos da produção de cana-de-açúcar sobre a produção de alimentos, o emprego, a estrutura fundiária e o meio ambiente - Muniz, Rômulo Santos (2012)
With the intensification of changing weather conditions on the planet, the debate on environmental issues is emphasized at the agenda of the international. The concern about the negative impacts to the environment and the continued use of fossil fuels has generated a search for alternative sources of cleaner energy. In this context, Brazil is inserted as a major supplier in the global renewable energy, proposing to be a major producer of biofuels in the world, mainly ethanol from cane sugar. This study aims at analyzing the impacts of the expansion of cultivation of cane sugar on food production, using as instruments to analyze the decomposition model \"shift-share\" and the scale and substitution effects. We also tried to determine the effects of farming on employment and land ownership structure, using as instruments of analysis regression models with panel data.